Rekonstruksi Kurikulum Pendidikan Islam dalam Menjawab Tantangan Modernitas dan Globalisasi - Basri B; Syarifuddin Ondeng; Syahruddin Usman (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The development of modernity and the forces of globalization have fundamentally transformed the landscape of human life, including the ways in which people acquire, produce, and utilize knowledge. These changes require Islamic educational institutions to reconstruct their curricula in order to remain relevant while preserving their Islamic identity. This study aims to examine the theoretical and philosophical foundations, curriculum content, as well as the teaching, learning, and assessment methods necessary for reconstructing the Islamic education curriculum in the contemporary era. This research employs a qualitative approach using the library research method. Data were collected from relevant books and national scholarly journals and analyzed descriptively and analytically through content analysis techniques. The findings indicate that the reconstruction of the Islamic education curriculum should be grounded in the principle of tawhid (Islamic monotheism) as an integrative paradigm while remaining open to advances in modern science through an integration–interconnection model that bridges Islamic and secular sciences. Furthermore, teaching and learning methods should shift from teacher-centered approaches to active learning strategies based on problem-based and project-based learning, accompanied by authentic assessment systems that measure twenty-first-century competencies such as critical thinking, creativity, collaboration, and communication, without neglecting students' spiritual and moral development. This study recommends that Islamic educational institutions develop curricula that are dynamic, adaptive, and responsive to contemporary needs while maintaining the authenticity of Islamic values.